Evaluation of different strategies to extract and preconcentrate penicillins present in milk prior determination by capillary electrophoresis. - Piñero, María Ysabel; Jurado, Natividad; Bauza, Roberto; Arce, Lourdes; Valcárcel, Miguel (Revista Científica de la Facultad de Ciencias Veterinarias, 2014)
Â One of the main problems concerning the determination of residues of penicillins (PENs) in complex matrix, as milk samples of animal origin, is the sample treatment. The aim of this work was to evaluate the influence of different background electrolyte (BGE) composition and pH, found in the literature, in the determination of PENs by capillary electrophoresis (CE) and, different sample treatments for the determination of PENs in bovine milk samples by CE. Off-line preconcentration, as classical solid-phase extraction (SPE) and QuEChERS (namely quick, easy, cheap, effective, rugged and safe) methodology and in-line preconcentration strategies, as large volume sample stacking (LVSS) were applied. In general, the milk sample treatment included protein precipitation prior to preconcentration. For this purpose, hydrochloric acid (HCl) and trichloroacetic acid (TCA) were mainly used. To evaluate the SPE steps, several commercial sorbents (Oasis HLB, Bond Elut C18 and Strata-X) were studied. In order to provide useful information enabling the determination of these analytes in routine laboratories, the strengths and weaknesses of each of the sample treatments tested are presented. Protein precipitation with HCl followed by SPE or QuEChERS procedure proved to be efficient for removing matrix interferences, showing higher selectivity than other procedures evaluated.